ICT: Didactic Strategy using Online Simulators for the Teaching Learning of the Law of Conservation of Matter and its Relationship to Chemical Reactions in Higher Middle Education - Barocio, Yvonne Rodriguez; Valdivia, Adolfo Eduardo Obaya; Vargas-Rodriguez, Yolanda M. (International Journal of Educational Technology and Learning, 2021)
It is imperative that a profound transformation be carried out in the traditional way in which we teach science subjects, so it is necessary that the role of student change from being a mere recipient of information to being the main player in the construction of his knowledge. One of the strategies to achieve this is to make use of ICT, within which are educational simulators, as a support resource to facilitate the teaching-learning processes taught in the classroom. The didactic strategy developed in this work was carried out with the PhET (https://phet.colorado.edu) simulator was used to improve the learning teaching of the law of conservation of the subject matter and its relationship with chemical reactions. To evaluate the learnings acquired by students, the Hake factor was determined. In terms of the implementation of this didactic strategy, students demonstrated greater recognition, understanding and appropriation of the knowledge gained about the importance of this law in chemical reactions. This teaching strategy is useful for higher middle-level schools that do not have a school science lab.